Efficiency between manual and mechanized loading system of oil palm Fresh Fruit Bunch (FFB) after harvest / Aidiel Aieka Othman - Othman, Aidiel Aieka (Faculty of Plantation and Agrotechnology, 2016)
This study was conduct to compare the efficiency between the manual and mechanical loading system used in FFB evacuation after harvested in oil palm plantation. It is done to find the most efficient system to be use in the plantation. The study was done by analysed the data of productivity, cost and hectare coverage. Malaysia palm oil plantation nowadays more depends on human labour especially in field operation. Dependant on the human labour will increase the cost and also affected the productivity. The human productivity in field operation is lower compare to the machine because machine can perform task more consistent than human. As the country that lead in oil palm industry, Malaysia need to invent and implement the modem technology that can contribute to the productivity of oil palm. The implementation of the machinery used in the plantation not only will solve the efficiency problem but also the labour shortage problem that facing by many countries. The contribution of MTG tractor in oil palm plantation proved that can increase the productivity, decrease the cost and increase the hectare coverage by the worker.